Integrated Collaborative Form of School and Parent Community In Shaping The Profile of Pancasila Students at Inpres Paccinongan Gowa Elementary School - Titi Mildawati; A. Marjuni; Muljono Damopolii; Baharuddin Baharuddin (Lembaga Bale Literasi, 2026)
This study aims to describe the integrated collaborative form between schools and the Orang Tua Peduli (Concerned Parents) community in shaping the Pancasila Student Profile at Inpres Paccinongan Elementary School, Gowa. The type of research used is descriptive qualitative with a pedagogical and phenomenological approach. The research location was at Inpres Paccinongan Elementary School, located on Jalan Bontotangnga, Somba Opu District, Gowa Regency. The data sources in this study consisted of the principal, teachers, and the chairperson and members of the Concerned Parents community as primary data. Secondary data was obtained from school documents, technical guidelines from the Concerned Parents community, and documentation in the form of photographs from interviews. Data collection was carried out through in-depth interviews, observations, and documentation using instruments in the form of interview guidelines and observation guidelines. Furthermore, the data was analyzed through a process of data reduction, data presentation, and conclusion drawing. The results of the study show that there are six forms of integrated collaboration between schools and the Orang Tua Peduli community, namely: (1) structured communication, (2) active participation in school activities, (3) involvement in program planning and evaluation, (4) periodic information dissemination, (5) home visits, and (6) parenting classes. These six forms of collaboration are carried out in an integrated and continuous manner in shaping the Pancasila Student Profile. All of these efforts are in line with the school's vision and mission